Vitamin D Deficiency Is Associated With Metabolic Risk Factors in Women With Polycystic Ovary Syndrome: A Cross-Sectional Study in Shaanxi China - Wang, Li; Lv, Shulan; Li, Fen; Yu, Xuewen; Bai, E.; Yang, Xiaofeng (Frontiers in Endocrinology, 2020)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women at reproductive age, which is characterized by obesity, hyperandrogenemia, and insulin resistance (IR). This study aimed to investigate the vitamin D status, and analyze the relationship between vitamin D deficiency and metabolic risk factors in PCOS women in Shaanxi China. Methods: A cross-sectional study included 169 women diagnosed with PCOS and 114 control women without PCOS. The serum 25(OH)D and metabolic markers were measured. Vitamin D deficiency was defined as serum 25(OH)D concentration less than 20 ng/mL. The primary outcome was the difference in vitamin D status between the PCOS and control groups, the secondary outcomes were correlations between serum 25(OH)D concentration and metabolic risk factors in women with PCOS. Results: The serum 25(OH)D concentration was significantly lower in women with PCOS than in controls (P < 0.05), and the prevalence rates of 25(OH)D deficiency and insufficiency were significantly higher in women with PCOS than in controls (P < 0.05). The serum 25(OH)D concentration was significantly lower in PCOS women with obesity or IR than in women without obesity or IR (P < 0.05), and the prevalence of 25(OH)D deficiency in PCOS women with obesity or IR was significantly higher than in women without obesity or IR (P < 0.05). Serum 25(OH)D concentration was significantly negatively correlated with body mass index (BMI), waist-to-hip ratio (WHR), fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), total cholesterol, low-density lipoprotein cholesterol (LDL-C), and high-sensitivity C-reactive protein (hs-CRP) (P < 0.05). In comparison, serum 25(OH)D concentration was significantly positively correlated with high-density lipoprotein cholesterol (HDL-C) (P < 0.05). Increased BMI and WHR, high levels of fasting insulin, HOMA-IR, total cholesterol, LDL-C and hs-CRP were regarded as risk factors, but high level of HDL-C was considered to be protective factor of vitamin D deficiency in PCOS women. Conclusions: Vitamin D deficiency is prevalent in PCOS women in Shaanxi China, especially in those with obesity and IR. The serum 25(OH)D level was correlated with metabolic risk factors in PCOS women. Multi-center randomized controlled trials with large sample sizes are needed to probe the metabolic effect of vitamin D supplementation in PCOS women.